Most Prevalent Causes of Divorce in Muslim Families during Covid-19 Pandemic: A Systematic Literature Review - Wahyu Abdul Jafar (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This research is important to determine the most prevalent causes of divorce in Muslim families during the Covid 19 pandemic. The research method used in this study is a systemic literature review, and this method will be applied to journals published in 2020-2022. There are four Research Questions (RQ) set in this study, so the final results obtained from this study are four; firstly, the wife is the party with the most initiative to sue for divorce during the Covid-19 pandemic. Second, the documentation technique is the most widely used data collection technique in research related to the causes of divorce during the Covid 19 pandemic. Third, economic factors are the most common factors causing divorce during the Covid-19 pandemic. In addition, it was also found that six other factors led to divorce. Fourth, mediation outside the court is the most widely used technique to prevent divorce during the Covid-19 pandemic. The important findings of this study are expected to contribute information to minimize the occurrence of divorce during the Covid-19 pandemic